2013
DOI: 10.1016/j.bbmt.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Complement Fragment 3a Priming of Umbilical Cord Blood Progenitors: Safety Profile

Abstract: Pre-clinical data showed that priming CD34+ hematopoietic progenitor cells (HPC) with complement fragment 3a (C3a) improved homing and engraftment. Thus, we hypothesized that priming of UCB hematopoietic progenitors with C3a would facilitate homing and could potentially be used to address the need for improved engraftment after UCB transplantation. We primed one of two UCB for double UCB transplant after nonmyeloablative conditioning. This design provided adequate safety and the potential to observe skewed lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…No adverse effects on survival and no infusional toxicities or activation of inflammatory pathways were observed. Engraftment of the C3a-treated UCB, however, was not impaired or favored relative to non-C3a-treated UCB [167].…”
Section: Complement Componentmentioning
confidence: 72%
See 1 more Smart Citation
“…No adverse effects on survival and no infusional toxicities or activation of inflammatory pathways were observed. Engraftment of the C3a-treated UCB, however, was not impaired or favored relative to non-C3a-treated UCB [167].…”
Section: Complement Componentmentioning
confidence: 72%
“…A simple priming of one UCB unit with C3a for 15 min followed by double UCB transplantation was performed in a phase I study [167]. No adverse effects on survival and no infusional toxicities or activation of inflammatory pathways were observed.…”
Section: Complement Componentmentioning
confidence: 99%
“…Double cord blood transplantation has been extensively investigated but, to date, a survival advantage has not been shown over single UCB units or unrelated donor grafts 7,28-37 and additional efforts are being investigated in clinical trials. 4,38,39 As these attempts are explored and potentially practice-changing data emerges, improvements and expertise in our current transplant procedures are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…This complement pathway protein is produced by bone marrow MSCs and interacts with the C3aR on UCB HSPCs to enhance CXCL12-mediated migration [100,101]. A Phase I clinical trial involving C3a priming of a one of the two UCB units in the nonmyeloablative conditioning double cord blood seting [101] did not, however, demonstrate preferable neutrophil recovery in the manipulated UCB unit in most cases, although the CD3 content of the graft correlated with engraftment. Lund et al [102] have reviewed this trial recently and concluded that the study has added value for designing further clinical trials using manipulated and unmanipulated double UCB units.…”
Section: IImentioning
confidence: 99%